The llobregat : The story of a polluted mediterranean river - Ginebreda, Antoni; Barceló, Damià; Sabater, Sergi (The Handbook of Environmental Chemistry, 2012)
The Llobregat belongs to the most thoroughly studied rivers in Europe and is a paradigm of the confluence of human and natural disturbances in a single basin. Because of its location in a very densely populated region and its Mediterranean character, the Llobregat supports a mixture of irregular flow, water abstraction, excess nutrients, mining debris, and a wide array of pollutants. The aquatic organisms strive to survive in a dramatically changing river that passes through a succession of dams, weirs and channels. The long-term river monitoring as well as the research that has been carried out in the river for a long time have provided an extensive knowledge of these disturbances and their effects on the biological communities. This book highlights the available information, with emphasis on the hydrological, chemical and biological elements interspersed in the river. Experts in the field discuss the main nutrient patterns and pollutant occurrence and the responses of the biological quality elements as well as the river ecosystem to the overall natural and man-made influences.